Do we more often opt for conservative management of ovarian tumors after changing the Dutch national guideline on enlarged ovaries? A nationwide cohort study - Esther Lems; Anna H. Koch; Sam Armbrust; Jaklien C. Leemans; Marlies Y. Bongers; Alicia Leon‐Castillo; Christianne A. R. Lok; Peggy M. A. J. Geomini (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Increasing evidence shows that conservative management of ovarian tumors classified as benign, based on ultrasound assessment, is safe. Therefore, conservative management has been adopted as the preferred strategy for certain ovarian tumors assessed as benign in the Dutch national guideline on enlarged ovaries in 2013. The aim of this study was to examine whether implementation of this guideline has led to changes in the number of women/100 000 women undergoing surgery for an ovarian tumor in the Netherlands. Material and Methods Histopathology reports were requested for all examinations of ovarian and fallopian tube specimens (including cyst enucleations) registered in Palga, the Dutch nationwide pathology databank, from 2011 (before guideline adaptation) and 2019 (after guideline adaptation). Reports on prophylactically removed adnexa, removal for other primary tumors (eg endometrial carcinoma), and for patients under 18 years of age, were excluded from the analysis. Interobserver agreement for the inclusion and classification of reports was assessed using Cohen's Kappa analysis. Results A total of 34 932 reports were retrieved, 13 917 of which were included in the analysis. In 2011 and 2019, respectively, 96.3/100 000 vs 68.8/100 000 women aged ≥18 underwent surgery for benign ovarian tumors, and 19.6/100 000 vs 18.3/100 000 for borderline and malignant tumors combined. The number of women/100 000 who had surgery for a benign ovarian tumor per 100 000 women declined by 28.5% (p < 0.001) between 2011 and 2019. The largest difference between 2011 and 2019 was observed in the number of women per 100 000 women who underwent surgery for a serous cystadenoma (−40.7%; 20.8/100 000 vs. 12.3/100 000), followed by endometrioma (−33.2%; 14.7/100 000 vs. 9.8/100 000), simple epithelial cyst (−57.3%; 8.4/100 000 vs. 3.6/100 000), and corpus luteum cyst (−57.0%; 4.0/100 000 vs. 1.7/100 000). Cohen's Kappa for the interobserver agreement was 0.96. Conclusions The number of women/100 000 undergoing surgery for a benign ovarian tumor has substantially decreased in the Netherlands when comparing data before and after implementation of the national guideline in 2013, while the number of women/100 000 undergoing surgery for a malignant or borderline tumor remained the same. These findings suggest successful implementation of the updated guideline, and a measurable effect on increased adoption of conservative management for benign‐looking ovarian tumors.